DERMOSCOPY OF INFLAMMATORY CONDITIONS: THE JOURNEY SO FAR - Balachandra S. Ankad; Savitha L. Beergouder (European Medical Journal, 2017)
The use of dermoscopy in general dermatological practice has recently increased. Its non-invasive nature means it is being practiced frequently by dermatologists to diagnose various skin conditions. Dermoscopy, also known as dermatoscopy, allows dermatologists to quickly visualise skin structures up to the papillary dermis level. The skin patterns seen under dermoscopy are usually due to pigment and vascular structures; melanin and haemoglobin play major roles and give different patterns depending on the skin condition and pathological changes. Many inflammatory diseases are encountered by clinicians in daily practice; at times they are indistinguishable to the naked eye and a biopsy is required to confirm the diagnosis. Dermoscopy is a useful tool in the diagnosis and differentiation of inflammatory skin conditions and is aptly termed inflammoscopy when used in these situations. Inflammoscopy demonstrates the distinct characteristic patterns of many conditions and aids accurate diagnoses. In this article, the importance of dermoscopy in the diagnosis of relatively common inflammatory conditions, such as eczema, psoriasis, lichen planus, pityriasis rosea, pityriasis lichenoides et varioliformis acuta, pityriasis lichenoides chronica, and discoid lupus erythematosus, is highlighted. Here, an overview of dermoscopic patterns in each of these conditions is emphasised.